Temperature Optimum of Mycobacterium leprae in Mice - Shepard, Charles C. (1965)
Shepard, Charles C. (Communicable Disease Center, Atlanta, Ga.). Temperature optimum of Mycobacterium leprae in mice. J. Bacteriol. 90:1271–1275. 1965.—Mycobacterium leprae multiplied most rapidly in foot pads of mice kept at an air temperature of 20 C. At air temperatures of 15 and 25 C, bacillary multiplication was slightly slower; at 10 and 30 C, distinctly slower; and at 4 and 35 C, no bacillary multiplication was detected. The temperature of the foot pad tissues of mice kept at an air temperature of 20 C averaged 27 to 30 C and that of mice kept at 10 and 30 C averaged about 25 and 36 C, respectively. These measurements indicate that the optimal temperature for the growth of M. leprae in mice is in the range several degrees above and below 30 C. The comparative effect of different air temperatures on the growth of M. leprae in foot pads was very similar to that found earlier for M. marinum in this site, thus indicating that the potential growth of M. leprae in vitro might have a similar optimum to M. marinum in vitro, i.e., 25 to 35 C. The optimal temperature for the growth of M. leprae appears to be the same in mice as in humans. It is pointed out that the temperature optimum of M. leprae may be a reflection of the fact that most of the bacilli being excreted into the environment, where they may reach new hosts, have multiplied in the nasal mucosa, a cool tissue.